Gray whale Eschrichtius robustus in Russian Far East: the history of discovery, research, and harvesting - Sergey A. Blokhin; Denis I. Litovka (Известия ТИНРО, 2014)
Discovery and research of gray whale in Chukotka are outlined and recent data on its whaling are presented on the base of authors’ and cited sources. The species was described for the first time in the late 16th century. Almost all its studies concerned the California-Chukotka population (East Pacific gray whale), whereas annual monitoring of the Korean-Okhotsk population started in 1995 only. Aboriginal nations of North America and Chukotka traditionally hunted on this whale: about 58 thousand whales of this species were landed in the period from 1600 to 1930, including 5,000 ones in Chukotka (8.6 %). Commercial whaling was developed at California in 1846-1890s and in the USSR waters in 1933-1937. Since 1937, the commercial whaling was banned and the gray whale harvesting for aboriginal people was permitted only. Scientific research of the gray whale started by biologists of the USSR Academy of Science in 1933 and continued till nowadays by Pacific Fisheries Research Center and its Magadan and Chukotka branches. The aboriginal whaling was realized from small motor-boats and kayaks by rifles and iron harpoons in the 1930s - early 1950s, from boats by large-calibre guns in 1956-1969. In total, 4060 whales were landed in 1922-1969. In 1969-1992, the whales for aboriginal people were landed by the whale-boat «Zviozdny». The aboriginal whaling from motor-boats by rifles and tilting handle-harpoons was renewed in 1994. Recently (since 1998) the quota is 135 gray whales per year, but real mean annual harvesting is about 110 whales, so only 2197 whales were landed in 1994-2013. The usual season for the whaling lasts from middle May till late November - early December. Taking into account the modern period of whaling, about 75 thousand of the East Pacific gray whales were landed in the period since 1600 to nowadays. Annual harvesting within the statutory quota does not influence negatively on the stock of this population. Moreover, increasing of the quota is available (aboriginal people can consume up to 350 whales annually) but the aboriginal whaling needs financial and material support for extending the harvesting.